MENGGUGAT KATA: ANALISIS PERNYATAAN PEJABAT TUN SEBAGAI OBYEK GUGATAN PADA PTUN DI INDONESIA - Mangara, Gerhard (Puslitbang Hukum dan Peradilan MA bekerja sama dengan Ditjen Badimiltun MA, 2023)
Science and practice related to state administrative courts in Indonesia have recently shown rapid development. Currently, lawsuits at the state administrative courts in Indonesia can not only be filed on state administrative decisions issued by the Government which is considered against the law but also include factual actions of the Government. This triggered a new discussion regarding the possibility that state administration officials' statements submitted in an official forum deemed to be against the law could be filed in a state administrative court in Indonesia based on an unlawful act by the government. This paper attempts to analyze the prospects and challenges of state administration officials' statements as objects of state administrative lawsuits in Indonesia based on the analysis of related decisions in Indonesia.